Sorption behavior of pomegranate polyphenols on surfactant-modified clays in aqueous solution - Houda Saad; Thouraya Turki; Mondher Srasra; Ezzeddine Srasra (Scientific African)
Purpose: Phenols are defined as primary pollutants. They can be present at high concentrations in the bulk effluents generated by the agro-food industries which can be toxic and have an impact on microbial processing in wastewater treatment plants. To address this challenge, a pretreatment process is needed. We investigate here, for the first time, the adsorption of pomegranate peels polyphenols on organophilic clays. Materials and methods: Organoclays were prepared by the intercalation of a cationic surfactant, hexadecylpyridinium bromide (HDPy), into purified Tunisian smectite clay at different Cation Exchange Capacities (CEC) degrees (0.5CEC, 1CEC and 2CEC). Surfactant-modified clays were characterized by X-ray diffraction (XRD) and Fourier Transform Infrared spectroscopy (FTIR). The adsorption study was conducted at different pHs and polyphenols concentrations. Adsorption isotherms were also established using the Langmuir and Freundlich models. Results: The results showed that the modification of clay by the cationic surfactant can increase polyphenols adsorption from 5.77 mg/g to 196.88 mg/g. This increase depends on the clay surfactant contents and the pH values. The retention process of polyphenols has been also studied. Depending on the surfactant content, it was revealed that both Freundlich and Langmuir models can describe the adsorption isotherms of pomegranate polyphenols. Conclusion: The 1CEC and 2CEC organo-clays are the interesting adsorbents for the removal of pomegranate polyphenols from aqueous media and wastewater. The best removal efficiency is of 98%. Fluorescence results suggested that the recovery of pomegranate polyphenols generated from beverage industries wastewater using HDPy-modified clays could be valorized as potential fluorescent pigments.